Periodontitis and Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD): An Interdisciplinary Perspective - Symonenko Рената (Actual Dentistry, 2026)
Modern medicine is increasingly moving away from local treatment of individual organs in favor of a systemic approach. One of the most striking examples of such a relationship is the combination of metabolic dysfunction-associated steatotic liver disease (MASLD) and periodontitis. The functioning of the oral cavity and liver as components of the digestive system has long been studied, but their role in maintaining systemic homeostasis has only recently attracted attention. Understanding environmental triggers of microbial pathogenicity and inflammatory mediators may open promising avenues for the prevention and treatment of periodontitis in patients with MASLD. A brief review of the available data on periodontal disease in patients with MASLD was conducted to provide treatment recommendations. Previous observational studies have shown a link between severe periodontal disease and worse outcomes in patients with MASLD. Further studies are needed to refine treatment recommendations for this group of patients. Importantly, the dentist may be the first specialist to detect metabolic abnormalities in a patient. Current knowledge suggests potential benefits of screening and treating periodontal disease in patients with liver disease. Conclusions. The etiology of liver disease may correlate with the development of periodontal disease, but further research is required to clarify their relationship and to develop interdisciplinary approaches to patient rehabilitation. Introducing MASLD screening in patients with refractory and severe periodontitis will enable a shift from “dental therapy” to comprehensive patient health management.